2007
DOI: 10.1007/s10535-007-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic stability, ex vitro rooting and gene expression studies in Hagenia abyssinica

Abstract: Randomly amplified polymorphic DNA (RAPD) markers were used to assess genetic stability of 80 micropropagated Hagenia abyssinica plants, 40 of axillary origin and 40 of adventitious origin. The shoots were isolated from the same mother tree and micropropagated for over two years. Among the 83 RAPD primers screened, 16 gave reproducible band patterns. These 16 primers produced 115 bands for each plant. One plant from axillary origin showed two unique bands with primer OPC-11. All other plants showed identical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…It was confirmed that micropropagated C. decidua plants obtained through leaves via adventitious shoot multiplication were genetically stable. Rady (2006), Feyissa et al (2007) and Gagliardi et al (2007) also confirmed complete similarity of adventitious shoot progeny with mother plant. Corresponding results were also observed in neem tree propagated in vitro (Singh et al 2002), chestnut (Carvalho et al 2004) and silver birch (Ryynanen and Aronen 2005).…”
Section: ⎯⎯⎯⎯supporting
confidence: 54%
“…It was confirmed that micropropagated C. decidua plants obtained through leaves via adventitious shoot multiplication were genetically stable. Rady (2006), Feyissa et al (2007) and Gagliardi et al (2007) also confirmed complete similarity of adventitious shoot progeny with mother plant. Corresponding results were also observed in neem tree propagated in vitro (Singh et al 2002), chestnut (Carvalho et al 2004) and silver birch (Ryynanen and Aronen 2005).…”
Section: ⎯⎯⎯⎯supporting
confidence: 54%
“…Somaclonal variation within micropropagated plants has been demonstrated using morphological, cytological, physiological, biochemical and molecular traits in several species (Martins et al 2004, Joshi andDhawan 2007). Various DNA marker techniques, including random amplified polymorphic DNA (RAPD), amplified fragment length polymorphism (AFLP), simple sequence repeats (SSR) and inter-simple sequence repeats (ISSR), have been developed and used to assess genetic stability within micropropagated plant ⎯⎯⎯⎯ lines (Gupta and Varshney 1999, Devarumath et al 2002, Carvalho et al 2004, Feyissa et al 2007. ISSR analysis involves the use of single simple sequence repeat (SSR) motifs in order to prime the polymerase chain reaction (PCR) and thereby amplify regions between adjacent, but inversely oriented, microsatellites (Zietkiewicz et al 1994).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…19,20) During the last few years, molecular techniques including various DNA markers such as restriction fragment length polymorphism (RFLP), random amplified polymorphic DNA (RAPD), amplified fragment length polymorphism (AFLP), simple sequence repeats (SSR) and inter-simple sequence repeats (ISSR), have been developed and profitably utilized for analyzing genetic fidelity of in vitro propagated plantlets as powerful and valuable tools. 19,[21][22][23][24][25] ISSR analysis, which uses the SSR primers annealing to and amplifying DNA sequence between the two adjacent, inversely oriented repeats, 26) was found to be the most economical among RFLP and RAPD. 27) In addition, ISSR technique is much more easily implemented than AFLP, and due to higher annealing temperatures and higher levels of polymorphism and/or reproducibility compared to RAPD markers, ISSR markers have been considered as an attractive alternative to RAPD markers.…”
mentioning
confidence: 99%